What should a Russian father be like? Exploring fatherhood norms and identifying norm patterns among inhabitants of Saint Petersburg. Issue 4 (September 2018) - Åberg, Pelle; Ekman, Joakim; Rodin, Johnny
Based on data from a survey conducted in Saint Petersburg in 2013, this article sheds new light on attitudes towards fatherhood in contemporary Russia. We explore what norms are held concerning fatherhood, how these attitudes are related to age, sex, education and income as well as to ideal–typical models established in previous research on fatherhood from Western Europe and the US. Thus, the article also discusses what explanatory value established theoretical models have for the Russian context. Norms of the role of the father in the family are related to general norms of masculinity and, hence, are an important part of the study of politics and the political climate in a society. The results show that there are several fatherhood ideals present in contemporary Northwestern Russia: a traditional breadwinner model, an active fatherhood model as well as what we refer to as a marginalized fatherhood model. The latter has not been substantially identified in previous research, and may tentatively be identified as a legacy of the Soviet era.